Influence of Water Quality on Exchange Phase-Solution Phase Behavior of Texturally Different Salt-affected Soils - and D.K. Sharma, Nirmalendu Basak S.K. Chaudhari (Journal of the Indian Society of Soil Science, 2016)
The influence of total electrolyte concentration (TEC) and sodium adsorption ratio (SAR) of water on ESR-SAR relationships of normal clay loam, saline silty loam and calcareous sodic loam soils was studied in a laboratory experiment. Twelve solutions, encompassing three TEC levels viz., 25, 50, and 100 me L-1 and four SAR levels viz., 5, 10, 20 and 30 mmol1/2 L-1/2 were prepared to equilibrate the soil samples using pure chloride salts of calcium, magnesium and sodium at Ca: Mg = 2:1. The SAR of equilibrium solution decreased as compared to the equilibrating solution and more so in waters of low salt concentration and low SAR. At all electrolyte concentration, SAR values were not attained to the equilibrium solution because of addition of Ca and Mg from mineral dissolution or supply of Ca and Mg from exchange sites. At higher TEC levels, considerable increase in exchangeable sodium percentage (ESP) was observed when it was correlated for anion exclusion and more so in calcareous sodic loam followed by saline silty loam and normal clay loam soils. Irrespective of TEC, the exchangeable sodium in all the soils increased by 2.1 to 3.8- fold and irrespective of SAR, it increased by about 1.1 to 2.1- fold, respectively. So, there is a positive interaction of TEC and SAR in sodification of soils. A positive interaction of TEC and SAR influenced the ESP build-up and CEC and silt + clay content played a major role in the visual disparity in sodification of these soils. Gapon’s selectivity coefficient values were perceptible in the order of calcareous sodic loam > saline silt loam > normal clay loam. This indicates the preference of normal clay loam soils for Ca2+ + Mg2+ than that of Na+ on the exchange complex, whereas loam soil exhibited high affinity for sodium. Regression coefficient of ESR-SAR relationships was maximum for sodic loam followed by saline silty loam and normal clay loam soil. The exchange equilibrium was strongly affected by TEC of the solution phase. Variation in soil pH was gradual with respect to TEC and SAR of equilibrating solution and a sharp change was observed. At a fixed TEC, critical ESP values were observed calcareous sodic loam followed by saline silt loam and normal clay loam . On the other hand, SAReq needed for critical ESP built-up was in the order of calcareous sodic loam > saline silt loam > normal clay loam. This may be because of dissolution of calcium bearing minerals in calcareous sodic loam; and wash out of calcium and magnesium from the exchange sites for saline silt loam soil.